Eukaryotic algal community composition in tropical environments from solar salterns to the open sea - Eckmann, Charlotte A.; Eberle, Jessica S.; Wittmers, Fabian; Wilken, Susanne; Bergauer, Kristin; Poirier, Camille; Blum, Marguerite; Makareviciute-Fichtner, Kriste; Jimenez, Valeria; Bachy, Charles; Vermeij, Mark J. A.; Worden, Alexandra Z. (Frontiers in Marine Science, 2023)
Tropical environments with unique abiotic and biotic factors—such as salt ponds, solar salterns, mangrove forests, and coral reefs—are often found in close proximity. The heterogeneity of these contrasting environments is reflected in rapid community shifts over short geographic distances, resulting in high biodiversity. While phytoplankton assemblages in coral reefs, particularly coral symbionts, have been well-studied, less is known about how they transition across tropical aquatic environments. We characterized phytoplankton communities by sequencing and analyzing plastid-derived 16S rRNA gene V1-V2 amplicons in and around Curaçao, an island in the Caribbean Sea. Alpha diversity varied more within salt ponds, salterns, and mangrove forests (highly dynamic habitats) than in more stable reef, off-reef, and open sea environments. Among eukaryotic phytoplankton, stramenopiles exhibited the highest relative abundances in mangrove forests, reefs, off-reef, and open sea environments, where cyanobacteria also showed high relative abundances. Green algae and cryptophytes were also present in these environments and reached highest relative abundances in salterns and salt ponds. Among stramenopiles, diatoms were more dominant in salt ponds and mangroves, while dictyochophytes and pelagophytes were increasingly important above reefs and farther offshore. Transitions in green algal lineages also followed a gradient from inland to offshore environments, wherein chlorophytes and prasinophyte class IV dominated in salt ponds, while prasinophyte Class II, including a newly described Ostreococcus bengalensis, had the highest relative abundances of green algae in mangrove forests, above-reef, off-reef, and the open sea, with additional differentiation within salt ponds that differ in connectivity to the sea. This study reveals the presence of multiple novel lineages within green algae and dictyochophytes as well as diversity of algae across tropical marine habitats.